Investing in Decentralised Power Generation – Financial Success Factors in South Africa's C&I Sector - Fineberg, Zack (Graduate School of Business (GSB), 2024)
In the context of a national energy crisis that has resulted in extreme load-shedding and constrained economic growth, the South African Government has introduced legislation and policies to enable private sector investment into power generation. This includes recent amendments to the Energy Regulation Act (ERA), the most important of which is an exemption from licensing requirements for generation facilities. As the largest power consumer, dominated by private ownership, the Commercial and Industrial (C&I) sector's investment in power generation represents the opportunity to increase the country's generation capacity with limited impact on the national fiscus. Using an exploratory multiplecase-study design, this study analyses and identifies the financial factors, mechanisms and barriers that enable or inhibit investment in decentralised generation (DG) by South Africa's C&I sector. The results indicate that (1) the reducing costs of photovoltaic technologies, (2) the emergence of specialised financial arrangements, such as Power Purchase Agreements (PPAs), and (3) tax incentives, enable investment by the C&I sector into DG by lowering financial barriers. Similarly, (4) increasing municipal electricity tariffs, and (5) the increasing intensity of load-shedding encourage the substitution of municipally supplied power for more affordable and reliable DG. In contrast, (1) the cost of battery technology, and (2) relatively low municipal feed-in tariffs constrain investment by disincentivising investment in DG at capacities required for the C&I sector to become entirely self-sufficient or net exporters of power. Finally, the results indicate that capital expenditure policies amongst business in the C&I sector, which are traditionally aimed at procuring production machinery, are not well suited to enable investment in DG.